The Vulnerability of Mantigola Bajo Household In Wakatobi Marine National Park - Isiyana Wianti, Nur; ., Suriana; La Ola, Taane; Tadjuddah, Muslim (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2018)
ABSTRACTThe purpose of this research is for describing vulnerability’s typologies by Bajo Mantigola household as a result of the prohibition of fishing activity in Maromaho reef, after the establishment of zonation and regional autonomy as the starting point of marine tourism development in Wakatobi Regency. The research was conducted from March to May 2017, on Bajo fishing community in Mantigola Village, South Kaledupa Subdistrict, Wakatobi Regency, South-east Sulawesi Province. This research was a descriptive study using quantitative research paradigm and supported by qualitative (post-positivistic) research. The results showed that based on a side of human capital, Bajo fisher head of households were a very low formal education. This fact have consequences to Bajo Mantigola households. They can not expand their livelihoods other than capture fisheries activities. In terms of social capital, Bajo fishermen’s households are relatively more vulnerable when they related to kaledupa land-dweller who do not provide opportunities for their economic development in Kampung Mantigola. Meanwhile, physical capital side, Bajo Mantigola Kampung is low in economic facilities such as the market, which should be a catalyst for economic development in the village of Bajo Mantigola. These four capital conditions eventually result in vulnerability to economic capital. Low income in the West wind season related to debt traps, consumptive attitudes, and less alternative income. The vulnerability can ultimately lead to illegal fishing practices that damage the environment due to the emergence of livelihood instability. And also, this paper will criticize the role of Bajo identity concerning to vulnerability dimension of The Bajo.Keywords: Vulnerability, Household, Mantigola Bajo, WakatobiABSTRAKTujuan penelitian ini yakni untuk mengetahui gambaran tipologi kerentanan yang dialami oleh rumahtangga nelayan Bajo di Mantigola akibat dari pelarangan kegiatan penangkapan ikan pada wilayah Karang Maromaho setelah terbentuknya TNKW dan otonomi daerah sebagai starting point pengembangan wisata Bahari di Kabupaten Wakatobi. Penelitian dilakukan pada bulan Maret hingga Mei 2017 di komunitas nelayan Bajo di Desa Mantigola, Kecamatan Kaledupa Selatan, Kabupaten Wakatobi, Provinsi Sulawesi Tenggara. Penelitian ini merupakan penelitian deskriptif menggunakan paradigma penelitian kuantitatif dan didukung oleh penelitian kualitatif (post-positivistic). Hasil penelitian menunjukkan dari sisi modal manusia, nelayan Bajo berpendidikan formal sangat rendah sehingga rumahtangga nelayan Bajo Mantigola tidak bisa memperluas mata pencaharian selain kegiatan perikanan tangkap. Dari sisi modal sosial, rumahtangga nelayan Bajo relatif lebih rentan ketika terkait dengan interaksi dengan orang darat, khususnya orang darat Kaledupa yang tidak memberikan peluang bagi berkembangnya perekonomian di Kampung Mantigola. Dari sisi modal fisik, Kampung Bajo Mantigola rendah dalam fasilitas ekonomi antara lain pasar, yang semestinya menjadi katalisator perkembangan ekonomi di kampung Bajo Mantigola. Kondisi empat modal ini akhirnya menghasilkan kerentanan pada modal ekonomi. Pendapatan rendah di musim angin Barat, rentan dengan jebakan hutang, sikap konsumtif, dan kurang alternative nafkah selain menangkap ikan. Kerentanan pada akhirnya bisa memicu timbulnya perilaku perikanan illegal yang merusak lingkungan akibat munculnya ketidakstabilan mata pencaharian. Tulisan ini juga mengkritisi peran identitas Bajo terhadap dimensi kerentanan orang Bajo.Kata Kunci: Kerentanan, Rumahtangga, Bajo Mantigola, Wakatobi